Recent Advances in Chemical Engineering Select Proceedings of ICACE 2015 - Regupathi, I.; Shetty K, Vidya; Thanabalan, Murugesan (Springer Nature Singapore : Imprint: Springer, 2016)
The book introduces the outcomes of latest research in the field of Chemical Engineering. The book also illustrates the application of Chemical Engineering principles to provide innovative and state of the art solutions to problems associated with chemical industries. It covers a wide spectrum of topics in the area of Chemical Engineering such as Transfer operations, novel separation processes, adsorption, photooxidation, process control, modelling, and simulation. The book provides timely contribution towards implementation of recent approaches and methods in Chemical Engineering Research. It presents chapters focussed on several Chemical Engineering principles and methodologies of wide multidisciplinary applicability. The intended audience of this book will mainly consist of researchers, research students, and practitioners in Chemical Engineering and allied fields. The book can also serve researchers and students involved in multidisciplinary research.